Handbook of waste management and co-product recovery in food processing. Volume 2 - Waldron, K. W. (Woodhead Publishing in food science, technology, and nutrition., 2009)
... An ideal information source for those involved in managing waste and recovering waste for use in products to produce revenue ... (Food Science and Technology - review of Volume 1)This is a most welcome addition to the literature, likely to be essential study material for both technologists and process engineers.(The Chemical Engineer - review of Volume 1)Food processors are under pressure, both from consumers and legislation, to reduce the amount of waste they produce and to consume water and energy more efficiently. Handbook of waste management and co-product recovery in.